A psychometric investigation of the South African career interest inventory-isiXhosa version among secondary school learners using the Rasch measurement model - Jansen van Vuuren, Nicola (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.